Structural Characterisation of ZnO Particles Obtained by the Emulsion Precipitation Method. (13th October 2012) - Kołodziejczak-Radzimska, Agnieszka; Markiewicz, Ewa; Jesionowski, Teofil
Abstract : Zinc oxide was obtained by precipitation in an emulsion system with zinc acetate used as a precursor of ZnO and potassium hydroxide or sodium hydroxide as a precipitating agent. The cyclohexane, as an organic phase, and a nonionic surfactant mixture were also used for preparation of the emulsion. By applying modifications of the ZnO precipitation process, such as changing the precipitating agent, composition of substrates, and the rate of substrate dosing, some interesting structures of ZnO particles were obtained. The morphology of the modified samples was analysed based on SEM (scanning electron microscope) and TEM (transmission electron microscope) images. Moreover the samples were characterised by determination of their dispersive properties using the noninvasive back scattering method (NIBS), adsorption parameters (BET), and crystalline structure (XRD). Thermogravimetric analysis (TG) as well as infrared spectrophotometry (FT-IR) was also applied. For selected samples their electrical properties (dielectric permittivity and electric conductivity) were also measured. The zinc oxide obtained consisted of particles in the shapes of solids, ellipsoids, rods, and flakes, with size ranging from 164 to 2670 nm and showed well-developed surface area with values as high as 20 m 2 /g.